Characterization of thyrotropin-releasing hormone producing neurons in sea urchin, from larva to juvenile - Cocurullo, Maria; Paganos, Periklis; Benvenuto, Giovanna; Arnone, Maria Ina (Frontiers in Neuroscience, 2024)
Most sea urchin species are indirect developers, going through a larval stage called pluteus. The pluteus possesses its own nervous system, consisting mainly of the apical organ neurons (controlling metamorphosis and settlement) and ciliary band neurons (controlling swimming behavior and food collection). Additional neurons are located in various areas of the gut. In recent years, the molecular complexity of this apparently “simple” nervous system has become apparent, with at least 12 neuronal populations identified through scRNA-sequencing in the species Strongylocentrotus purpuratus. Among these, there is a cluster of neurosecretory cells that produce a thyrotropin-releasing hormone-type neuropeptide (TRHergic) and that are also photosensory (expressing a Go-Opsin). However, much less is known about the organization of the nervous system in other sea urchin species. The aim of this work was to thoroughly characterize the localization of the TRHergic cells from early pluteus to juvenile stages in the Mediterranean sea urchin species Paracentrotus lividus combining immunostaining and whole mount in situ hybridization. We also compared the localization of TRHergic cells in early plutei of two other sea urchin species, Arbacia lixula and Heliocidaris tuberculata. This work provides new information on the anatomy and development of the nervous system in sea urchins. Moreover, by comparing the molecular signature of the TRHergic cells in P. lividus and S. purpuratus, we have obtained new insights how TRH-type neuropeptide signaling evolved in relatively closely related species.